ACQUISITION OF SENATE MEMBERS IN 2024 AND THEIR EFFECTS ON THE THAI POLITICAL SYSTEMS. - Sittichockkaewmoon, Pisanupong (Journal of MCU Phetchaburi Review, 2024)
What will Thai politics be like? It depends on the actions of the country’s legislative and executive branches, which consist of: Members of the House of Representatives (MPs), who are elected by the people, and Members of the Senate (Senators), who are currently people who are related to groups of 20 occupations, running to be elected as senators. and filter among themselves using a method that is a world phenomenon, namely “How Candidates Choose Each Other” Among the groups of election candidates, which will be selected from the district, provincial, and national levels. The acquisition of such senators will be controversial and questionable as to how much transparency there will be. How consistent are the people who run with the professional groups? What is the importance of senators in the political system? We will get to know the origins and importance and possible predictions about the future of Thailand’s political system with the acquisition of this new set of senators.